Assessment of treatment for functional posterior cross-bites in patients at the deciduous dentition phase - Dutra,André Luiz Tannus (2004)
The aim of this study was to clinically assess the results of treatment for functional posterior cross-bites by means of selective grinding in individuals at the deciduous dentition phase over a period of 12 months. From a total of 1,011 children examined in the 2-to-6-year age bracket, 26 with functional posterior cross-bites were selected. The sample was divided into 2 groups of 13 children each, group 1 receiving the treatment proposed and group 2 serving as the control group. Treatment was followed up by exercises designed to alter the children's muscular memory. The results showed that correction of functional posterior cross-bite was achieved for all the children treated, the correction remaining stable 12 months later. No self-correction of malocclusion occurred among the control group.